Investigating the relationship of disguised socialbots and disinformation threat in Taiwan - Trisha T. C. Lin (International Telecommunications Society (ITS), 2022)
Taiwan has faced bot driven disinformation campaigns during elections and COVID 19 outbreaks. Although past studies suggest ill agenda socialbots accelerate and deteriorate disinformation influences, their relationship has not been examined quantitatively yet. To fill the research gap, this study aims to investigate the comp lex associations between socialbot attitude and disinformation interaction and related factors affecting disinformation threat. Disguised socialbots in this study refer to fake accounts to engage in malicious online activities via anthropomorphic social me dia interactions. A modified Theory of Planned Behavior (TPB) model is adapted to examine h ow socialbot attitudes and disinformation interaction are associated with perceived bot control and privacy concern, which influences disinformation threat. This web survey examines 750 Taiwanese socialbot users' perceptions and attitudes towards disguised socialbots in August 2021. Structural equation modeling (SEM) results show that socialbot attitude is positively associated with perceived bot control and disinform ation interaction, but is not related to privacy concern. Disinformation interaction is positively associated with perceived bot control and privacy concern. That is, negative attitudes towards malicious socialbots result in users' increasing perceived bot control and competence with disinformation interaction. Additionally, the more interaction with disinformation, the higher degree of perceived bot control and privacy concern about socialbots. Moreover, perceived bot control and privacy concern predicts disinformation threat. Implications are discussed.
Keywords: 330; Socialbot; disinformation; Theory of Planned Behavior; perceived bot control; privacy concern